2011
DOI: 10.4028/www.scientific.net/amr.266.171
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Memory Behavior of Poly(L-Lactide)/Poly(ε-Caprolactone) Blends

Abstract: Poly(L-lactide) and poly(ε-caprolactone) (PLLA/PCL) blends with various weight ratios were compounded by melt mixing and their shape memory properties were investigated. The thermal properties, surface morphology and dynamic mechanical properties of the blends were characterized. The results demonstrate that the introduction of PCL improves the process of crystallization of PLLA whereas the reverse situation is for PCL. PLLA/PCL blends were found to exhibit an immiscible behavior from the characterizations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Dong et al [23] reported a pioneering work on shape-memory material based on PLLA/PCL blends in 2011. They reported that PLLA/PCL blend with the weight ratio of 1:3 presents a R r of about 95% within 22s.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Dong et al [23] reported a pioneering work on shape-memory material based on PLLA/PCL blends in 2011. They reported that PLLA/PCL blend with the weight ratio of 1:3 presents a R r of about 95% within 22s.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, biodegradable SMPs are of increasing interest for applications in various areas. Many works have reported that polylactic acid (PLA) and its copolymers have a mild SM effect. , In order to further improve the performance, clays such as kaolinite, montmorillonite, halloysite, etc., have been employed to prepare PLA-based SM composites. Before composite preparation, organic modification for clays is necessary to be done because the surface treatment not only enhances the compatibility between clays and PLA but also helps to achieve a uniform dispersion of clays.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular architecture or molecular deformation mechanism, is another essential factor in achieving shape memory behavior 52,53 . The molecular architecture of SMEs must consist of net‐points (the hard phase or fixed phase) and switching units (the soft phase or reversible phase), which allow the structure to be deformed, maintained, and recovered under applied force and external activation 54,55 . Recently, Chien et al 56 studied shape memory characteristics of SME‐based waterborne biodegradable polyurethane.…”
Section: Overviews Of Smesmentioning
confidence: 99%
“…52,53 The molecular architecture of SMEs must consist of net-points (the hard phase or fixed phase) and switching units (the soft phase or reversible phase), which allow the structure to be deformed, maintained, and recovered under applied force and external activation. 54,55 Recently, Chien et al 56…”
Section: Overviews Of Smesmentioning
confidence: 99%